2020
DOI: 10.3389/fbioe.2020.00116
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Intervention for Spastic Upper Extremity Improves Lower Extremity Kinematics in Spastic Adults: A Collection of Case Studies

Abstract: Methods: Three patients with an anoxic brain injury, upper extremity spasticity, and an altered gait participated in this study. A specific treatment plan based on the patient was tailored by the orthopedic hand surgeon to help release the contractures and spastic muscles. Three-dimensional gait analysis was performed before surgery, 3, 6, and 12 months postoperatively. During each experimental session, the patient walked at a self-selected pace in a straight line across four force plates embedded into the flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
(72 reference statements)
1
7
0
Order By: Relevance
“…Participants who used walking aids said they could more easily hold on to the aid, which they felt increased their walking capacity. This ameliorating effect was described after treatment of UL with botulinum toxin [39,40] and surgery [41]. Moreover, the participants also noted a generally improved posture when standing, sitting, and lying down.…”
Section: Discussionsupporting
confidence: 55%
“…Participants who used walking aids said they could more easily hold on to the aid, which they felt increased their walking capacity. This ameliorating effect was described after treatment of UL with botulinum toxin [39,40] and surgery [41]. Moreover, the participants also noted a generally improved posture when standing, sitting, and lying down.…”
Section: Discussionsupporting
confidence: 55%
“…Studies that did not mention the screening of medications that might affect muscle tone. previous study reported spatiotemporal parameters of gait could be improved by releasing the upper extremity spasticity ( 46 ). therefore, the present study excluded trials that did not specifically screen the application of spasticity medication in accordance with a published study.…”
Section: Methods and Analysismentioning
confidence: 97%
“…Among the 22 reviewed studies, 19 (86.36%) provided level III evidence, and 21 (95.45%) obtained a low or very low score on the GRADE scale (Table 3) [39,40] (Figure 2). Sixteen studies were retrospective case series [12,17,18,[21][22][23][24][26][27][28][29][30][31][32][33]37], two were single-center [25] or multi-center [38] retrospective cohort studies, three were prospective case series [34][35][36], and one was a randomized controlled trial [16]. Only three studies included a comparative group, formed by patients who were treated with rehabilitation in two [16,38] and those undergoing a different surgical technique in the third [25].…”
Section: Quality Of Evidencementioning
confidence: 99%
“…Only two articles studied candidates for functional surgery [26,29], reporting on a total of 56 patients (5.96% of patients in reviewed studies). In the remaining studies, the patient sample was mixed, with functional and nonfunctional hands or hands of unspecified status [21,28,30,[34][35][36][37][38]41]. None of the reviewed studies stratified their outcomes according to the etiology of the upper extremity spasticity or the patient profile.…”
Section: Patient Profilementioning
confidence: 99%